COOPERATION OF EDUCATIONAL INSTITUTIONS TRAINING INDUSTRIAL PERSONNEL WITH FOREIGN COUNTRIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In today's globalized world, industrial workforce training institutions play a crucial role in economic development. This article examines the significance of international collaboration in vocational education, the benefits of joint training programs, and the challenges faced by institutions. The study highlights successful models from leading countries and provides recommendations for improving cross-border cooperation in industrial workforce development.